Rice proteins and cod proteins forming shared microstructures with enhanced functional and nutritional properties. (30th August 2021) - Wang, Ren; Wang, Tingting; Feng, Wei; Wang, Qichu; Wang, Tao
Highlights: Protein co-assemblies were prepared using rice proteins and cod proteins. The solubility of rice proteins increased from 1.7% to 92.7%. The co-assembled proteins acquired leveraged amino acid compositions. Abstract: Low water solubility strictly limits the potential applications of plant or animal proteins such as rice proteins (RPs) and cod proteins (CPs). In this study, nanoscale hydrophilic colloidal co-assemblies (80 150 nm) with excellent water solubility were prepared by hydrating RPs and CPs at pH 12 combined with neutralization. The solubility of RPs was boosted to over 90% (w/v), while most of the subunits in CPs became fully soluble. Structural analysis revealed that RPs and CPs non-covalently reacted, which triggered sheet-helix transitions and formed a compact core of RPs coated by a layer of CPs. Both proteins exposed significant hydrophilic motifs and buried hydrophobic moieties, contributing to the high water-dispersibility of their co-assemblies. Moreover, the co-assembled proteins acquired leveraged amino acid compositions between RPs and CPs. This study will enrich the processing technology of protein components, customizing their structural and nutritional characteristics.